Streaming Audio with Bluetooth : A Deep Dive into A2DP and LE Audio - Sayanna Chandula,; Jyothiprakash Reddy Thukivakam, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The evolution of Bluetooth audio streaming has been significantly shaped by the adoption of various audio codecs, with A2DP (Advanced Audio Distribution Profile) and AVRCP (Audio/Video Remote Control Profile) serving as its foundation. These codecs each come with their own set of trade-offs, which include bitrate, latency, compatibility, and power usage. While Bluetooth technology has seen advancements in terms of versions and capabilities, current implementations still face limitations. These limitations have paved the way for the emergence of Bluetooth Low Energy Audio as a potential solution to address the challenges related to power consumption, particularly in specific use cases. This article provides a detailed comparison of existing audio codecs supported in A2DP, highlighting the limitations of classic Bluetooth audio and how LE Audio's enhancements address those challenges.
Keywords: Bluetooth Audio Streaming; Audio Codecs; Power Efficiency; Bluetooth Profiles; Wireless Connectivity; Low Complexity Codec